5q Minus Myelodysplasia Associated with Multiple Epithelioid Granulomas within Conventional Renal Cell Carcinoma. (16th July 2012) - Matnani, Rahul G.; Patel, Roshan K.; Strup, Stephen E.; Karabakhtsian, Rouzan G.
Abstract : A 69-year-old Caucasian female, with a previous diagnosis of 5q minus myelodysplastic syndrome, presented with conventional renal cell carcinoma (RCC) associated with multiple-epithelioid nonnecrotizing granulomas. Two previous reports of sarcoidosis, primarily involving the lung and skin, have been described in patients with 5q minus myelodysplasia. A cluster of closely linked genes encoding for cytokines such as IL-4, IL-5, and IL-3 are present on chromosome 5q. Hence, in sarcoidosis, cytokine imbalances associated with the deletion of these cytokine genes have been postulated. However, an occurrence of epithelioid granulomas within a carcinoma, in preexisting clonal myelodysplastic syndrome, has not been described. The patient, in the current study, had long standing 5q minus deletion, clinically characterized by refractory anemia associated with hypolobated megakaryocytes. However, the patient's history was negative for sarcoidosis and the extensive nonnecrotizing epithelioid granulomas were confined within RCC. Due to the absence of Th-2 cytokines, such as IL-4 and IL-5, in a subset of 5q minus myelodysplastic syndrome, proinflammatory Th-1 cytokines such as IFN- γ and TNF- α may be exaggerated in an environment conducive to antigen expression. Hence, we propose a greater susceptibility for the development of granulomas, at least in a subset of patients with 5q minus myelodysplasia.